1998
DOI: 10.1159/000017028
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of Ser 199/202 Phosphorylated Tau in a Case of Frontotemporal Dementia

Abstract: We examined a 65-year-old patient with clinicopathological features that met the criteria of frontotemporal dementia (FTD), particularly frontal lobe degeneration (FLD). He came from a family with concentrated occurrence of dementia symptoms in the presenium. Neuropathological examination disclosed brain atrophy locally pronounced on the frontotemporal lobes with characteristic neuronal loss, microvacuolation and astrocytic gliosis. There were no pathological hallmarks such as senile plaques, Pick bodies (PBs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Degenerating neurons contained abnormal inclusions that were immunoreactive with antibodies specific for phosphorylated tau protein (see Fig 2B). As reported previously, 39 tau-positive inclusions were also present in glial cells. Classic Pick bodies, neurofibrillary tangles, and neuritic plaques were not observed.…”
Section: Neuropathological Findingssupporting
confidence: 88%
See 3 more Smart Citations
“…Degenerating neurons contained abnormal inclusions that were immunoreactive with antibodies specific for phosphorylated tau protein (see Fig 2B). As reported previously, 39 tau-positive inclusions were also present in glial cells. Classic Pick bodies, neurofibrillary tangles, and neuritic plaques were not observed.…”
Section: Neuropathological Findingssupporting
confidence: 88%
“…Wide, twisted ribbons made of four-repeat tau have also been described in families with the ϩ3 and ϩ16 intronic mutations. 5,11,19,38 The tau pathology of FTD-K is both neuronal and glial, 39 as is that in other families with mutations in the intron following tau exon 10. 1,46 The discovery of mutations in the tau gene in FTDP-17 has shown that dysfunction of tau causes neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunostaining studies identified tau abnormalities in the absence of neurofibrillary tangles. 37,46,47 The biochemical data demonstrating that 4Rtau isoforms accumulate selectively as insoluble aggregates in the brains of P301L patients confirm that only those tau isoforms containing the microtubule binding repeat encoded by exon 10 (ie, 4Rtau) are affected. Because neurofibrillary tangles are composed of all six tau isoforms, the absence of neurofibrillary tangles is not surprising in these patients with FTD.…”
Section: Common Clinical Featuresmentioning
confidence: 85%